2016
DOI: 10.30979/rev.abeno.v16i4.350
|View full text |Cite
|
Sign up to set email alerts
|

O método de aprendizagem baseada em problemas na disciplina de Radiologia Odontológica

Abstract: Na presente pesquisa propôs-se avaliar a opinião de estudantes de Odontologia quanto à experiência vivenciada mediante aplicação da aprendizagem baseada em problemas (Problem-Based Learning - PBL) na disciplina de Radiologia Odontológica. A amostra foi composta por 138 estudantes de uma instituição de ensino privada, sendo a maior parte do gênero feminino (75,20%, n = 104). Houve predomínio da faixa etária de 19 a 20 anos (39,59%, n = 56), de estudantes oriundos de escolas públicas (62,19%, n = 86) e com renda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…However, the sociocultural and psychological backgrounds of the students from different countries should be considered 18 . In Brazil 29 , the traditional teachinglearning method is still the most used and widespread approach. This situation may cause some discomfort common to any process of change and adaptation to students and be one of the reasons why, in this study, the PBL did not provide better performance to students, as observed in previous studies 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the sociocultural and psychological backgrounds of the students from different countries should be considered 18 . In Brazil 29 , the traditional teachinglearning method is still the most used and widespread approach. This situation may cause some discomfort common to any process of change and adaptation to students and be one of the reasons why, in this study, the PBL did not provide better performance to students, as observed in previous studies 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Quando questionados sobre o método de sua preferência para aprendizado, venceu o método tradicional, pois consideraram que teriam um melhor aproveitamento da disciplina e não gostariam de estudar em uma universidade na qual todas as disciplinas utilizassem ABP. Considerou-se que esse dado poderia advir do fato de os estudantes não estarem familiarizados com a técnica e que um grande número ficar insatisfeito com a pontuação final obtida na avaliação 24 .…”
Section: Discussionunclassified
“…Many Universities from different countries are concerned about university teachers thinking and pedagogical skills, and, therefore, are researching and offering training in order to improve them (Gibbs & Coffey, 2000;Gibbs & Coffey, 2004;Postareff, Lindblom-Ylanne, & Nevgi, 2007;Stes, Gijbels, & van Petegem, 2008;Prosser & Trigwell, 1997). For the past decades, some innovative teaching approaches are being held in Brazil, mostly related to technology use (Caliari, Zilver, & Perez, 2017), Problem-Based Learning in Business (Escrivão Filho & Ribeiro, 2008;Borochovicius & Tortella, 2014) Med (Coelho Filho, Soares, & Sa, 1998;Galvão, Azevedo-Vaz, & Oliveira, 2016) and Technology Schools (Ribeiro, 2008;Garcia, 2014) or Gamifying Education (Fragelli & Fragelli, 2017;Silva Junior, 2017).…”
Section: Introductionmentioning
confidence: 99%